2019 IEEE International Workshop on Information Forensics and Security (WIFS) 2019
DOI: 10.1109/wifs47025.2019.9034985
|View full text |Cite
|
Sign up to set email alerts
|

Group Membership Verification with Privacy: Sparse or Dense?

Abstract: Group membership verification checks if a biometric trait corresponds to one member of a group without revealing the identity of that member. Recent contributions provide privacy for group membership protocols through the joint use of two mechanisms: quantizing templates into discrete embeddings, and aggregating several templates into one group representation.However, this scheme has one drawback: the data structure representing the group has a limited size and cannot recognize noisy query when many templates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recently [5,6,7] proposed a framework based on aggregation and embedding of several biometric signatures into a unique vector representing the members of a group. It has been demonstrated that this allows a good assessment of the membership property at test time provided that the groups are small.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [5,6,7] proposed a framework based on aggregation and embedding of several biometric signatures into a unique vector representing the members of a group. It has been demonstrated that this allows a good assessment of the membership property at test time provided that the groups are small.…”
Section: Introductionmentioning
confidence: 99%